Pengaruh Sodium Hidroksida dan Hidrogen Peroksida terhadap Rendemen dan Warna Pulp dari Serat Daun Nenas The Effect of Sodium Hydroxide and Hydrogen Peroxide on the Yield and Color of Pulp from Pineapple Leaf Fiber - Holia Onggo; Jovita Tri Astuti (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Chemical pulping process of pineapple leaf fiber with sodium hydroxide (NaOH) and bleaching process of pulp with hydrogen peroxide (H2O2) were conducted to see the influence of treatment on the yield and the color of the pulp produced. Raw materials were cayenne type pineapple leaf of 6~7 months old from Subang, West Java. Color was measured with a Portable Color Difference Meter Model CDX-105 with CIE 1976 L*a*b* (CIELAB) method.The result showed that  NaOH and H2O2 can be used for bleached pulp making. The pulp yield of the treatment decreased but their lightness of the color increased. The optimum pulp properties were obtained by using 10% NaOH  at 100°C and solid to liquid ratio 1:20 at 1 hour cooking time. The yield was 73% and value of L* around 84.6. By using 2% H2O2, the yield decreased 7.6% but the value of L* increased to 92.2.  The color of the pulp was white.  Value of the different color (DE*ab) compare to the white standard is 8.7. Decreasing of its yield caused by dissolving of  lignin, non fiber and pigment.